(6u-3v+1)(3u+v)=0

Simple and best practice solution for (6u-3v+1)(3u+v)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6u-3v+1)(3u+v)=0 equation:


Simplifying
(6u + -3v + 1)(3u + v) = 0

Reorder the terms:
(1 + 6u + -3v)(3u + v) = 0

Multiply (1 + 6u + -3v) * (3u + v)
(1(3u + v) + 6u * (3u + v) + -3v * (3u + v)) = 0
((3u * 1 + v * 1) + 6u * (3u + v) + -3v * (3u + v)) = 0
((3u + 1v) + 6u * (3u + v) + -3v * (3u + v)) = 0
(3u + 1v + (3u * 6u + v * 6u) + -3v * (3u + v)) = 0

Reorder the terms:
(3u + 1v + (6uv + 18u2) + -3v * (3u + v)) = 0
(3u + 1v + (6uv + 18u2) + -3v * (3u + v)) = 0
(3u + 1v + 6uv + 18u2 + (3u * -3v + v * -3v)) = 0
(3u + 1v + 6uv + 18u2 + (-9uv + -3v2)) = 0

Reorder the terms:
(3u + 6uv + -9uv + 18u2 + 1v + -3v2) = 0

Combine like terms: 6uv + -9uv = -3uv
(3u + -3uv + 18u2 + 1v + -3v2) = 0

Solving
3u + -3uv + 18u2 + 1v + -3v2 = 0

Solving for variable 'u'.

The solution to this equation could not be determined.

See similar equations:

| c^2+8=0 | | -6+y=75 | | 5+7=-3 | | 3,75x=2,50x+20 | | (6-7i)(8-3i)=0 | | 4y+24x=60 | | -2+x=62 | | 9h-25=38 | | y-55=106 | | 7y-9=-7y+19 | | 3+2h=19 | | 5x=30x-20 | | -3r+-1=14 | | 5+-2k=1 | | 8x-3+5x=2x+4-4x | | 12x+17=13x+16 | | k-33=-55 | | -x^2+4x-5=-2 | | 7x+5+3x+15=180 | | 7(5x+9)=18(x+9) | | h-16=-36 | | j-31=-203 | | 4x+31+x+24=90 | | 10=-2r+-6 | | -(3-2X)=2X-3 | | 6x-3+7x=2x+4-4x | | m-5=96 | | 6=3h+3 | | y=500x+25 | | y=-10x+130x-400 | | 1x-4=2x+2 | | 4 = t2+ 2 |

Equations solver categories